Approximate Competitive Equilibria in Large Economies - Matthew O. Jackson; Alejandro M. Manelli (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1994)
We examine market-clearing prices and allocations in economies where agents' demand functions are undominated relative to their beliefs about other agents' actions. For sufficiently large economies and give certain restrictions on beliefs, the resulting allocations are nearly competitive.
Keywords: 330